EFEKTIVITAS Trichoderma sp. METABOLIK DAN Pseudomonas fluorescens TERHADAP PENYAKIT BUSUK LUNAK PADA TANAMAN KOL BUNGA (Brassica oleracea var. Botrytis L.) - Juliana O. Runtukahu; Berty H. Assa; Guntur S.J. Manengkey (Universitas Sam Ratulangi, 2016)
ABSTRACTThe purpose of this study is to see Efektivitas Microorganisms antagonists Trichoderma sp.Metabolic and Pseudomonas fluorescens against Rot Disease on Plant Cauliflower for 4 months,namely from March to June 2016 in the Village Paslaten District of Tomohon East and in theLaboratory of Microbiology and Plant Pathology, Faculty of Agriculture, University of SamRatulangi Manado. Research in the laboratory to observe microscopically cause soft rot cauliflowerplants.This research was conducted using the method of randomized block design with 3 treatments,treatment A control without application of microorganisms antagonistic, treatment B withapplication of microorganisms antagonistic Trichoderma sp. metabolic, and treatment C withapplication of microorganisms P. fluorencens. this treatment is repeated 10 times. With ratingsplants infected with the disease formula presentation. The variables measured were presenting thenumber of infected leaves and cauliflower infected.The results showed that of some microorganismused, the most effective at controlling soft rot disease on a cauliflower is Pseudomonas fluorencensobservation with the end result obtained was 30%, followed by Trichodermasp. metabolic 40%.Treatment antagonistic microorganisms is also seen to be effective in inhibiting disease infection onthe leaves of the plant before the formation of flowers.Kata kunci :Efektivitas, Cauliflower, Erwinia carotovora, Pseudomonas fluorescens, Trichodermasp. Metabolic.